EFEKTIVITAS KONSELING KELOMPOK TEKNIK RELAKSASI UNTUK MENGATASI KESULITAN BELAJAR PESERTA DIDIK SMP PGRI 1 PALEMBANG - Arizona Arizona (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2017)
The objectives of this research are: (1) to know the effectiveness of group counseling and to overcome student's learning difficulties in SMP PGRI 1 Palembang, (2) to know effectiveness of group counseling model with intrumental music based relaxation technique to overcome student learning difficulties SMP PGRI 1 Palembang. This reasearch use Quantitative approach Quasi-experimental design method with Non equivalent Control Group Design was conducted to obtain an overview of the effectiveness of group counseling through instrumental music-based relaxation techniques to overcome the learning difficulties of SMP PGRI 1 Palembang students by the following steps: (1) preparation of control groups and experimental groups, 2) provide a pre-test in the control and experimental group (3) provide treatment or treatment to the experimental group (4) provide post test in the experimental group, (5) the final outcome of group counseling effectiveness with instrument music-based relaxation techniques to overcome learning difficulties students. This study resulted in the effectiveness of group counseling with intrumental music-based relaxation techniques to overcome student learning difficulties. The study involved 14 students as a sample of 7 as an experimental group and 7 as a control group. Based on the results of field tests, the level of self efficacy of students increased after following group counseling activities with self-relaxation techniques. Shown by changes in student's learning difficulty level before being given treatment (preliminary evaluation) and after (final evaluation) of 147 points or 99%. The result of statistical test of wilcoxon test also shows 0,005 <0,05 so it can be concluded that group counseling service with intrumental music based relaxation technique is effective to overcome student's learning difficulties.keywords: group counseling, instrumental music, learning difficulties, relaxation.